A comparative study on the efficacy of drotaverine and valethamate on cervical dilatation during labour - Sinhasane, Hema; GM, Nishty (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The most common cause of prolonged first stage of labour is cervical spasm leading to cervical dystocia. Many times it is observed that inspite of good uterine contractions; cervix fails to dilate or dilates very slowly. This is functional cervical dystocia. Methods: On admission detailed history was taken, complete general physical examination was made. Careful obstetric examination confirmed the lie, presentation, position of the foetus and FHP. Vaginal examination was made and the state of cervix (Dilatation, consistency and effacement) station of the vertex and type and adequacy of the pelvis was noted. Results: A slight increase in the cervical tear is noted in the multrigravida in Group II. The incidence of PPH was double that of Group III. This was observed specifically when the drug was given after 5cms of dilatation of cervix. Conclusions: The maternal adverse effects were more with valethamate. Though there was transient fetal tachycardia with valethamate, the fetal outcome remained the same in all the groups.